Stereoselektiver Aufbau von Naturstoffgrundgerüsten auf Basis Prolin-haltiger Diketopiperazine - Deppermann, Nina; Justus Liebig University Giessen (My University, 2009)
In dieser Arbeit wird ein Diversitäts-orientiertes, effizientes und stereoselektives Synthesekonzept für die Darstellung hoch-funktionalisierter Diketopiperazin-Grundgerüste vorgestellt. Solche Grundgerüste finden sich in einer Vielzahl von Naturstoffen mit interessanten biologischen Eigenschaften wie Tryprostatine, Marcfortine oder Brevianamide. Als Precursor für die Synthese dieser Grundgerüste wurden enantiomerenreine Azabicycloalkane aus einer diastereoselektiven hetero-Diels-Alder-Reaktion verwendet.Die hier vorgestellte Syntheseroute ermöglicht die Darstellung rigider Grundgerüste mit variabler Stereochemie, Geometrie und Ringgröße in wenigen Stufen und hohen Ausbeuten. Die generelle Anwendbarkeit dieses Konzepts wurde durch die Synthese Valin-haltiger Di- und Tripeptidmimetika für Screenings gegen IL-8 sekretierende Caco-2-Zellen geprüft. Die Synthese spirocyclischer Naturstoffe wie Spirotryprostatin A wurde durch eine Pd-katalysierte alpha-Arylierung von o-halogenierten Anilin-Derivaten anvisiert.Eine systematische Überprüfung von Katalysatoren, Lösungsmittel und Reaktionsbedingungen ergab ein optimiertes Protokoll für die Spirocyclisierung komplexer cyclischer Edukte. Dabei wurde sowohl die Schutzgruppenstrategie optimiert als auch der Effekt von Nachbargruppen und Heteroatomen untersucht. Auf Basis dieser Erkenntnisse wurde eine neue Synthesestrategie für Spirotryprostatin A erstellt.

In this work, a diversity-oriented, efficient and stereoselective synthesis route to highly functionalized proline-based diketopiperazine scaffolds was established. These scaffolds are enclosed in a number of natural products with interesting biological profiles such as the Tryprostatines, Marcfortines or Brevianamides.The precursors are azabicycloalkanes, which can be obtained from a diastereoselective hetero-Diels-Alder-reaction in defined but variable stereochemistry and ring sizes. The herein described route provides the opportunity to tailor rigid scaffolds with variable stereochemistry, geometries and ring sizes in a short and high yielding route. The general application of this concept has been proven by the synthesis of valine-containing di- and tripeptide mimetics for screening against IL-8 secreting Caco-2-cells involved in inflammatory processes.The synthesis of natural products like spirotryprostatines A was envisioned through a Pd-catalyzed alpha-arylation of o-halogenated aniline-derivates as first described by Hartwig and coworkers.A series of model substrates was designed that were cyclised to oxindoles. Screening through a number of catalysts, solvents and reaction conditions yielded an optimised protocol for the spirocyclisation of cyclic compounds. A protecting group strategy was optimised and the effect of neighbouring groups and incorporated heteroatoms was investigated. A new concept for the total synthesis of Spirotryprostatine A on the basis of these insights has been developed.
Stereoselective Synthesis of Proline-based Natural Product Scaffolds
Keywords: Naturstoffe; Diketopiperazine; Stereoselektive Synthese; Pd-Katalyse; Heck-Cyclisierung; Natural Products; Diketopiperazines; stereoselective synthesis; Pd-catalysis; Heck-Cyclization; ddc:540